Genetic analysis of RPA single-stranded DNA binding protein in Haloferax volcanii - Stroud, A. L. (2012)
Replication protein A (RPA) is a single-stranded DNA-binding protein that is present in all three domains of life. The roles of RPA include stabilising and protecting single- stranded DNA from nuclease degradation during DNA replication and repair. To achieve this, RPA uses an oligosaccharide-binding fold (OB fold) to bind single- stranded DNA.